STATUS OF TOMATO VIRUSES IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Tomato (Solanum lycopersicum L.) is an important crop, extensively cultivated as vegetable and fruit worldwide for its nutritional supply of vitamins, minerals, antioxidants and carbohydrates to humans. Its production in Nigeria is dominated by poor resource peasant farmers as their major means of livelihood. Virus diseases have been considered as an economically important biotic factor mitigating profitable tomato production during wet and dry seasons of Nigeria. The increase in number of new viruses and emergence of host resistance-breaking strains of known virus species causing significant yield losses on tomato is of great concern and these vary from one location to another. The status of research on viruses infecting cultivated tomato in Nigeria is discussed
Keywords: Tomato, viruses, status, Nigeria